Vitamin E profile in rice (Oryza sativa L.) seeds grown and commercialized in Costa Rica - Conejo-López, Valery (2022)
Introduction. Rice (Oryza sativa L.) is one of the most consumed cereals worldwide, the indica and japonica subspecies are the most cultivated. The vitamin E present in rice has a high antioxidant activity that contributes to extend the longevity of its seeds. Its quantification allows to know the nutritional contribution of this vitamin. Objective. To analyze the vitamin E profile in seeds of indica (registered commercial, aromatic, promising in development) and japonica subspecies of rice (O. sativa L.), consumed in Costa Rica. Materials and methods. Twenty-seven materials grown in the Chorotega and Brunca regions of Costa Rica, harvested in 2020 were analyzed. Vitamin E was quantified by ultra-high performance liquid chromatography coupled to triple quadrupole mass detection with chemical ionization source at atmospheric pressure at the Centro para Investigaciones en Granos y Semillas (CIGRAS), Universidad de Costa Rica, in 2021. Results. In the vitamin E profile, a characteristic clustering was obtained for the japonica samples, which was opposite to that presented by the indica samples. The majority compounds were γ-tocotrienol, α-tocopherol, and γ-tocopherol, the range of total vitamin E concentration was 5.50 to 33.20 μg g-1, where the japonica subspecies reported the lowest amount (6.30 – 8.80 μg g-1), while the Nayuribe sample, belonging to the registered commercial indica subspecies, obtained the highest concentration (33.20 ± 7.40 μg g-1). Conclusion. Although the analyzed subvarieties are phylogenetically from the same species, the significant differences found in the nutritional intake of vitamin E may be due to intrinsic characteristics of each subspecies. The significantly high vitamin E content in the Nayuribe sample showed that it is possible to find stocks for a high vitamin E content among the varieties analyzed.